Peranan Kreativitas Guru terhadap Motivasi Belajar Peserta Didik Sekolah Dasar - Ira Rahmayuni Jusar; Mudjiran Mudjiran (Departement of Mathematics Education, 2022)
This study aims to determine the role of an elementary school teacher on students' learning motivation. One of the elements that influence the success of a student is motivation. If students have the drive to learn, then they will achieve the desired learning outcomes. In an effort to produce quality learning and education, teachers must be creative. To encourage motivation to acquire the principles of the creed, the teacher must be able not only to understand the teaching material but also various learning methods and designs. The findings show that teachers can increase students' motivation in learning in various ways, including by providing teaching materials, using various teaching techniques, managing classes, and utilizing learning media. High learning motivation will lead to the best results, the task of a teacher is to foster student motivation. The research methodology in research is a literature review (library research) available in online or offline libraries. The main component in learning, motivation can support and encourage learning. According to literature findings, students with high levels of motivation are more likely to try hard, dress impeccably, and not want to give up. They are also more likely to engage actively in reading to improve learning outcomes and solve problems. On the other hand, people who are unmotivated, appear disinterested, get discouraged easily, and don't pay attention to what they are learning will have difficulty in school.